2017
DOI: 10.4103/jmp.jmp_3_17
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid conformal planning technique with solitary dynamic portal for postmastectomy radiotherapy with regional nodes

Abstract: Purpose:This study focuses on incorporation of a solitary dynamic portal (SDP) in conformal planning for postmastectomy radiotherapy (PMRT) with nodal regions with an intention to overcome the treatment planning limitations imposed by conventional techniques.Materials and Methods:Twenty-four patients who underwent surgical mastectomy followed by PMRT were included in this study. Initially, a treatment plan comprising tangential beams fitted to beam's-eye-view (BEV) of chest wall (CW) and a direct anterior fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Adequate target coverage is associated with tumour control which leads to improve biochemical relapse-free survival, cancer progression-free survival and cancer-specific survival. Several studies [8][9][10][11][12][13][14][15][16]20,22,23,26,27,30 have reported similar PTV_eval coverage for breast cancer patients. Tanaka et al 16 investigated the FIF technique with lung blocks for breast radiotherapy and reported V 95% and V 100% of 93•2 and 62•7% for patients treated with the FB technique.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adequate target coverage is associated with tumour control which leads to improve biochemical relapse-free survival, cancer progression-free survival and cancer-specific survival. Several studies [8][9][10][11][12][13][14][15][16]20,22,23,26,27,30 have reported similar PTV_eval coverage for breast cancer patients. Tanaka et al 16 investigated the FIF technique with lung blocks for breast radiotherapy and reported V 95% and V 100% of 93•2 and 62•7% for patients treated with the FB technique.…”
Section: Resultsmentioning
confidence: 99%
“…This is achieved using two tangential fields to treat the intact breast or chest-wall and an anterior and sometimes opposed posterior fields to treat the regional lymph nodes in the upper axillary and supraclavicular regions. 3,[19][20][21][22][23][24][25][26][27] There are several techniques used for breast radiation therapy including the use of wedges, field-in-field (FIF), hybrid technique (involving open and optimised fields), intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT). Several studies have reported that using IMRT, VMAT, FIF or the hybrid technique to treat the breast and regional lymph nodes have greater target coverage, reduced hotspots and reduced doses to the organs at risk (OAR) compared to conventional treatment with wedges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations